Paeonol inhibits human lung cancer cell viability and metastasis in vitro via miR‐126‐5p/ZEB2 axis. Issue 2 (12th October 2021) - Lv, Jing; Zhu, Shibing; Chen, Huiping; Xu, Ying; Su, Qingyu; Yu, Guofen; Ma, Wei
Abstract: Paeonol exerted an effect in lung cancer, but the underlying mechanism remained vague. In this research, we assessed the effects of Paeonol and microRNA (miR)‐126‐5p on the viability, migration, invasion, and epithelial‐mesenchymal transition (EMT) of lung cancer cells. Lung cancer cells and BEAS‐2B cells were treated with Paeonol, and viability was detected by 3‐(4, 5)‐dimethylthiahiazo (‐z‐y1)‐3, 5‐di‐ phenytetrazoliumromide (MTT) assay. The migration and invasion of lung cancer cells after treatment with Paeonol at 40 μg/mL or 80 μg/mL were detected by wound healing assay and Transwell assay, respectively. The effects of Paeonol on transforming growth factor‐β1 (TGF‐β1)‐induced EMT and relative expressions of EMT‐related proteins were determined using Western blot. The target gene of miR‐126‐5p and the binding sites between them were predicted by TargetScan, and confirmed using dual‐luciferase reporter assay. Relative expressions of miR‐126‐5p, its target gene and EMT‐related proteins were determined by quantitative real‐time polymerase chain reaction (qRT‐PCR) and Western blot. Rescue assay was performed to analyze the relation between Paeonol and miR‐126‐5p. Paeonol down‐regulated cell viability and inhibited migration, invasion and TGF‐β1‐induced EMT while up‐regulating miR‐126‐5p expression in lung cancer cells as the dose increased. However, miR‐126‐5p inhibitor could reverse the effect of Paeonol. ZEB2 was the target gene of miR‐126‐5p, and silencing ZEB2 expression reversed the effects of miR‐126‐5p downregulation. Paeonol also regulated the expression of ZEB2 in lung cancer cells, and this regulation depends on the regulation of miR‐126‐5p. Paeonol inhibits human lung cancer cell viability and metastasis via the miR‐126‐5p/ZEB2 axis, and could be adopted as a potential agent for lung cancer treatment.